4.5 stars for this hotel : user-generated content and its impact on hotel decision-making - Lopes, Ricardo Filipe Marçal (2021)
With an undeniable importance in several areas, social media changed consumers, who are not only more demanding but also, they have the information in a click distance, and tourism is not an exception. Tourists use social media before, during and even after a trip, but user-generated content is not just about sharing. The content generated by other consumers is also a source of information and therefore is used as electronic word-of-mouth, since that same content will be available and will be used by other tourists during the decision-making process. However, the impact that different types of user-generated content have on consumers’ hotel decision-making process is still unclear. This study is aimed to understand not only how positive and negative user-generated content impact the process of deciding a hotel, in particular hotels in the European city centers, but also which type of user-generated content (pictures or reviews) has more impact as electronic word-of-mouth in that same decision-making process. The conclusion is that these two types of user-generated content are perceived by consumers as unseparated content, meaning that consumers are not able to only consider reviews or pictures separately, since they consider that these types of content complement each other.